Peran Pemerintah Kota Dalam Menanggulangi Kecelakaan Lalu Lintas Di Kota Bandar Lampung Akibat Kerusakan Infrastruktur Jalan - Adelia Maharani; Rifqi Fahrozi; Adelita Ayu Nurhaliza (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
This study aims to find out the parties who are related and responsible according to Law Number 38 of 2004 concerning roads (Road Law), for various damage to road infrastructure in the city of Bandar Lampung and their handling and government accountability to parties who are disadvantaged in problems this (273 Law Number 22 of 2009). This study uses normative juridical research with data sources consisting of primary, secondary and tertiary data, analyzed using qualitative data analysis techniques. Data that can be obtained from written materials such as laws, books and documents. And also by using empirical legal research, by using a statutory approach and a case approach, data collection was carried out by means of literature studies and interviews, the data collected was descriptive. (113) Law enforcement for traffic accidents caused by damaged roads, especially in the city of Bandar Lampung, is not only a form of public service, but is a responsibility mandated by law, which if not implemented can lead to serious legal consequences. This study aims to determine law enforcement against traffic accidents caused by damaged roads in the city of Bandar Lampung and what factors become obstacles to law enforcement against traffic accidents caused by damaged roads in the city of Bandar Lampung. The results of research on traffic accident law enforcement due to damaged roads in the city of Bandar Lampung show the weak handling of the traffic police and the Bandar Lampung city government in implementing Law number 22 of 2009 concerning Road Traffic and Transportation, especially article 273. As well as the effectiveness of law enforcement and implementation that occurred in the implementation of the current road is still considered lacking.